Cryptographic Symmetry Analysis with AES Algorithm for Safeguarding Data at Government Agencies - Muhammad Rizal; Elviawaty Muisa Zamzami; Muhammad Zarlis (IJISTECH (International Journal of Information System and Technology), 2019)
Data is very confidential information because it contains important information about the company or agency. Therefore it is necessary to secure these important data, in order to avoid misuse, theft of information or manipulation by certain parties who are not responsible. To avoid theft and manipulation of data it is necessary to implement a computer-based security system. One of them is by using cryptography. Cryptography is the study of how to change information from a normal (understandable) state / form into an incomprehensible form. One method that can be used to secure messages or information is the Advanced Encryption Standard (AES). AES is a part of symmetry cryptography. The application of AES cryptographic algorithms in securing data at government agencies can produce encryption that cannot be understood by humans and produce decryption that is exactly the same as the initial plaintext inputted, so that important government data can be secured in such a way. This research will produce a program that can encrypt and decrypt data using the AES (Advanced Encryption Standard) algorithm which will be used to secure data at Government Agencies.